Assessing Habitat, Distribution, and Characterization of Crickets (Orthoptera Gryllidae) - Odhiambo, Martha Akello (JOOUST, 2023)
Edible crickets can act as an alternative source of food and feed when production from conventional plants and animals is disrupted. Natural habitats for the crickets continue to shrink and fragment due to climate change as well as anthropogenic pressures. Although habitat loss has been reported as the main cause of species extinction, knowledge on the habitat requirements of edible insects is scanty. The objectives of this study were to: (i) assess the distribution of crickets based on habitat preference (ii) determine the effects of temperature on development and survival of crickets (iii) characterize the cuticular hydrocarbons that generate desiccation resistance in the crickets and (iv) characterize the morphological diversity of haemocytes associated with cellular immunity in the crickets. A survey was conducted in Western Kenya to assess the distribution of crickets based on habitat preference. Thirteen descriptive variables were used to create a habitat distribution model. Akaike information criteria (AIC) was applied to estimate the habitat preference for each cricket species. The effects of temperature on the development, and survival of crickets were determined at six constant temperatures (18, 22, 26, 30, 34 and 38 0C). The cuticular hydrocarbon profiles of cricket species were identified and quantified by gas chromatograph – mass spectrometry (GC-MS). To assess the morphological diversity of haemocytes, hemolymph smears were prepared, and microscopic examinations made. The results indicated that the cricket species can be classified into three groups, Group I (Acheta domesticus and Diestrammena asynamora) which preferred areas near settlement, Group II (Scapsipedus icipe, Gryllus bimaculatus, and Brachytrupes membranaceus) that preferred fields and grasses, and Group III (Gryllotalpa africana) that preferred wet lands. The optimum temperature estimated for egg-to-adult development ranged from 26 ˚C to 34 ˚C. Further, a homologous series of n- alkanes, alkenes, and methyl branched alkanes were identified. Haemocytes were classified into six distinct types with prohaemocytes, plasmatocytes and granulocytes being the most numerous cells in the hemolymph of the crickets. This study concludes that the most preferred habitats for crickets are natural vegetation, areas near water bodies, having high shelter density and away from human settlement. In addition, the results suggest that the long chain cuticular hydrocarbons increase with increase in temperature of the cricket’s habitat and provide greatest protection against desiccation. Understanding how insects adapt and survive under stress and identifying the physiological processes that occur during that time may allow us to better conserve their habitat and prevent species extinction.
Keywords: Edible crickets; cricket distribution; cricket habitat